Dental pulp stem cells - A basic research and future application in regenerative medicine - Stefańska, Katarzyna; Volponi, Ana Angelova; Kulus, Magdalena; Waśko, Jadwiga; Farzaneh, Maryam; Grzelak, Joanna; Azizidoost, Shirin; Mozdziak, Paul; Bukowska, Dorota; Antosik, Paweł; Zabel, Maciej; Podhorska-Okołów, Marzenna; et al. (Biomedicine & pharmacotherapy Biomedecine & pharmacotherapie, 2024)
Dental pulp is a valuable and accessible source of stem cells (DPSCs) with characteristics similar to mesenchymal stem cells. DPSCs can regenerate a range of tissues and their potential for clinical application in regenerative medicine is promising. DPSCs have been found to express low levels of Class II HLA-DR (MHC) molecules, making them potential candidates for allogeneic transplantation without matching the donor's tissue. Research on the correlation between non-coding RNAs (ncRNAs) and human dental pulp stem cells (DPSCs) provides promising insights into the use of these cells in clinical settings for a wide range of medical conditions. It is possible to use a number of ncRNAs in order to restore the functional role of downregulated ncRNAs that are correlated with osteoblastogenesis, or to suppress the functional role of overexpressed ncRNAs associated with osteoclast differentiation in some cases.
Keywords: regenerativní lékařství; buněčná diferenciace; RNA, Untranslated; Cell Differentiation; Stem Cell Transplantation; Stem Cells; kmenové buňky; Animals; Humans; zubní dřeň; lidé; Regenerative Medicine; zvířata; nekódující RNA; Dental Pulp; transplantace kmenových buněk